Investigating the Factors that may contribute to the Learning of Children at ISO Quality Certified and Non-Certified Pre-Schools in the United Arab Emirates - GANDHI, VANDANA KUMAR (2017)
The purpose of this study is to examine the quality of learning in pre-schools and to understand the differences in children’s learning between ISO quality Certified and Non-certified pre-schools, thereby exploring the importance of quality certifications in pre-schools in the UAE. The study which is based on the learning theories from Piaget and Vygotsky, explored global and local literature that assert the importance of quality pre-schooling. The review on ISO certification principles and research indicate linkages to quality in EYE settings. The study uses mixed methods with strong attention to the quantitative method. This is a longitudinal study that looks at the trends of the growth in learning at the preschool level and the learning outcomes of ISO quality certified and non-certified preschools exploring the trends through test results over period in several schools using trend analysis. A survey was conducted to gain the perceptions of parents and the quality time they spend with children at home. Finally, interviews were conducted with school leaders and parents of the preschools to understand their perception on leadership and quality in learning. The results point to the importance of quality certifications at pre-schools, leadership influence on the quality at schools and that the involvement of caregivers affects the learning and socialization of the pre-schoolers. The students at the ISO quality certified pre-schools have demonstrated higher ability to learn and acquire skills. The implications of these results are timely and crucial for the UAE, in the absence of sufficient research done on the early year’s education and quality certification. The study claims that quality of learning of children in pre-schools in the UAE is enhanced through certification such as ISO. In addition, the study further asserts that leadership practices and parental involvement reinforce quality learning among pre-schoolers.